The Effect of the Implementation of Reward, Incentive, and Punishment Methods on Employee Performance at PT. Anugerah Alam Berastagi - Ice Monika Br Torus Pane; Andre Fitriano; Theresia Monalisa Br Tarigan; Sintia Perbinia Br Ginting; M. Tahir (Journal of Research in Business, Economics, and Education, 2023)
The purpose of this research is to find out whether the application of the reward, incentive, and punishment methods affect the performance of employees at PT. Anugrah Alam Berastagi. This research approach is based on a quantitative approach. The population in this sample in this study consists of 53 employees. Data collection techniques used questionnaires, interviews, and documentation studies. The use of data analysis will use multiple linear regression analysis. The results of the partial hypothesis testing obtained a t-count > t-table or 4.380>2.009 and a significance of 0.000 < 0.05, so partially the reward has a positive and significant effect on the performance of PT. Anugrah Alam Berastagi employees. The results of the partial hypothesis testing obtained a t-count > t-table or 2.226 > 2.009 and a significance of 0.000 < 0.05, so partially the incentive has a positive and significant effect on the performance of PT. Anugrah Alam Berastagi employees. The results of the partial hypothesis testing obtained a t-count > t-table or 4.478 > 2.009 and a significance of 0.000 < 0.05, so partially it can be concluded that punishment has a positive and significant effect on the performance of PT. Anugrah Alam Berastagi employees. The test results obtained an F-count (28.486) > F-table (2.79) and a significance probability of 0.000 < 0.05 means that simultaneously rewards, incentives, and punishment have a positive and significant effect on the performance of PT. Anugrah Alam Berastagi employees.